Genomic evidence of speciation reversal in ravens - Anna M. Kearns (Nature Portfolio, 2018)
Speciation reversal is known mainly from recently diverged lineages that have come into secondary contact following anthropogenic disturbance. Here, Kearns et al. use genomic and phylogenomic analyses to show that the Common Raven (Corvus corax) was formed by the ancient fusion of two non-sister lineages of ravens.